Business popularity analysis from twitter - Yaisawas, Pajaree; Lerdsri, Sukanlaya; Thanasopon, Bundit; Netisopakul, Ponrudee (My University, 2018)
Social media is increasingly utilized for sharing information of online products, from business owners to customers, as well as among customers themselves. In order to utilize these sharing information, this paper proposes and demonstrates the methodology for analyzing business brand popularity based on Twitter posts. The analysis can be visualized by implementing a web application that keeps track and analyzes Twitter posts mentioning about cosmetic and beauty product. Specifically, the application focuses on Twitter posts in Thai; and its key features are, (1) identifying brands being in trend, (2) analyzing and virtualizing statistics provided by Twitter, and (3) classifying Twitter posts’ sentiment into positive, negative and objective. The website provides useful insights to brand owners aiming at exploiting social media and to customers buying products from those brands.
Keywords: Brand; Hashtag; Popularity; Sentiment analysis; Social listening; Social media analysis; Twitter